2010
DOI: 10.1111/j.1474-9726.2010.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial restoration of T‐cell function in aged mice by in vitro blockade of the PD‐1/ PD‐L1 pathway

Abstract: SummaryProgrammed cell death-1 (PD-1) is a newly characterized negative regulator of immune responses. The interaction of PD-1 with its ligands (PD-L1 and PD-L2) inhibits T-cell proliferation and cytokine production in young mice. Increased PD-1 expression has been described during chronic infections, inducing chronic activation of the immune system to control it. As aging is associated with chronic immune activation, PD-1 may contribute to ageassociated T-cell dysfunction. Our data showed the following result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 57 publications
7
112
0
Order By: Relevance
“…It has been proposed that impaired T‐cell function during aging is associated with an increase in the population of PD‐1‐expressing T cells (Channappanavar et al ., 2009; Shimada et al ., 2009; Lages et al ., 2010; Decman et al ., 2012). To address the relationship between the exhaustion of T cells and aging more specifically, we examined the expression of Tim‐3, which, along with PD‐1, defines T‐cell exhaustion during chronic infection or in tumors (Jin et al ., 2010; Sakuishi et al ., 2010) but has never been studied in a model of aging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that impaired T‐cell function during aging is associated with an increase in the population of PD‐1‐expressing T cells (Channappanavar et al ., 2009; Shimada et al ., 2009; Lages et al ., 2010; Decman et al ., 2012). To address the relationship between the exhaustion of T cells and aging more specifically, we examined the expression of Tim‐3, which, along with PD‐1, defines T‐cell exhaustion during chronic infection or in tumors (Jin et al ., 2010; Sakuishi et al ., 2010) but has never been studied in a model of aging.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the previous study, most Tim‐3 − PD‐1 + cells are of the memory phenotype (CD44 hi ) and that a large numbers of these cells are EM cells (Fig. 2A,B) (Lages et al ., 2010). In contrast, Tim‐3 + PD‐1 + CD8 + T cells are mostly CD62L lo T cells, and the expression levels of CD44 in these cells are mainly distributed from intermediate to low, which characterizes them as revertant phenotype cells (Figs 2A,B, and S2) (Akbar & Fletcher, 2005; Lages et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T cells become exhausted with age, losing functionality for unclear reasons that could include long‐term antigenic stimulation or chronic inflammation (Lages et al ., 2010). PD‐1 is an exhausted T‐cell marker (Barber et al ., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, long‐term eRapa reduced phenotypically exhausted T cells that can be functionally impaired and contribute to age‐related immune dysfunction (Lages et al ., 2010). Gene array data showed that PD‐1 + cells in eRapa‐treated mice had reduced signature exhaustion gene expression suggesting better function versus PD‐1 + control T cells.…”
Section: Discussionmentioning
confidence: 99%